Genetic Diversity in Three Sinipercine Fishes Based on Mitochondrial D-Loop and COX1 Sequences - Minghui Lin; Xu-Fang Liang; Ke Lu; Ming Zeng; Junjie Gao; Yaqi Dou; Yulan Kuang; Qiwei Zhang (Fishes, 2025)
Mandarin fish (Siniperca chuatsi), golden mandarin fish (Siniperca scherzeri), and Coreoperca whiteheadi are three important aquaculture species in China facing several threats to their production. Genetic diversity was assessed by sequencing the mitochondrial D-loop and cox1 regions in 207 individuals across nine populations. The genetic diversity analysis, based on the concatenated sequences, revealed that the total haplotype diversity was high across all sinipercine fish populations. Population differentiation analysis revealed that most genetic variation was within populations: 74.5% in S. chuatsi (p